Son biased investments and old age support - Christine Ho (Asian Development Bank Institute (ADBI), 2017)
Son biased investments are common in many Asian countries where sons are customarily responsible for providing old age support to parents. Using data from the China Health and Retirement Longitudinal Study, I find that parents invested nearly twice more in sons than in daughters in terms of college education spending and marriage gifts value. Conversely, parents received relatively higher marginal returns to investment from daughters than from sons in terms of living proximity, monetary and in-kind transfers, and help with instrumental activities of daily living. Family fixed effects models as well as an instrumental variable strategy are employed to control for the potential endogeneity of parental investments in children. The results indicate that daughters may be reciprocating parental monetary investments in their education and marriage by increasing old age support. The findings suggest that daughters may be a viable source of support to parents and that encouraging parental investments in them may lead to an increase in family provided old age support.
Keywords: D13; I26; J13; J14; J16; 330; son bias; parental investment; old age support; reciprocity